Poverty and Social Exclusion in Bosnia and Herzegovina : Insights from the 2011 Extended Household Budget Survey - Ceriani, Lidia; Ruggeri Laderchi, Caterina (World Bank, Washington, DC, 2015)
In 2011 the statistical authorities of Bosnia-Herzegovina collected for the first time a national survey which allows monitoring the European indicators of poverty and social exclusion as well as national indicators of absolute and relative consumption poverty. The Extended Household Budget Survey (EHBS) adds extra modules to a standard Household Budget Surveys (HBS) designed to collect detailed information on household expenditures. The additional modules covered the information needed to measure poverty and social exclusion in EU Member states. In this way, the EHBS represents a hybrid solution between collecting a HBS and a Survey of Income and Living Conditions (SILC), the official tool for measuring poverty and social exclusion in the EU, which omits expenditure information. The note is structured as follows: section two presents a detailed description of the data, while section three discusses the three constituent indicators of AROPE, and their mutual relation, i.e. their union (the AROPE indicator) and their intersection. Section four presents additional dimensions of exclusion on which data have been collected, especially those relating to children. Section five presents a comparison of indicators of monetary poverty and social exclusion. Finally, section six summarizes the most interesting elements which have emerged from this analysis and concludes.